PERANCANGAN MIDDLEWARE UNTUK MENGHUBUNGKAN SISTEM INFORMASI DAGANG DENGAN APLIKASI E-FAKTUR DARI DIREKTORAT JENDERAL PAJAK - Tony Wijaya (Universitas Raharja, 2017)
Since July 1st, 2016, every entrepreneur in Indonesia must implement e-Faktur application from Indonesia Taxation Authority. The objective is to ease entrepreneurs to report the company’s tax and provide more detailed information about product and service offered by entrepreneurs. For most of companies that already have information system, implementation of e-Faktur application means they have to do double work to input operational data into two different applications. The objective of this research is to design a middleware that can connect trade information system so it can export data to e-Faktur application. This middleware is designed using Agile Methodology with Extreme Programming approach which value working software feature.Tested with black box methodology to ensure exported data is correct. It has feature to adjust decimal so it will be very accurate. It also very easy to operate, save operational time, increase tax accuracy dan ease entrepreneur to report tax to government.